Nitrogen uptake of cocoa seedlings as a response of cocoa pod husk derived liquid organic fertilizer application in combination with urea - Erwin Prastowo; Irawan Dwiyanto; Setyo Budi Santoso (Indonesian Coffee and Cocoa Research Institute, 2021)
As nitrogen (N) has played an important role in cocoa production, both providing the N-sources alternative materials, and increasing the efficiency of fertilization are urgently required to support both crop and land productivity. Research aims to investigate the N uptake of cocoa seedlings as results of combination of liquid organic fertilizer (LOF) and urea application. To support the understanding in terms of N dynamics, SPAD (Soil Plant Analysis Development) chlorophyll content, N use efficiency (NUE) and recovery of applied nitrogen (REN) were determined with additional information related to the optimal dosage of urea to be applied to cocoa seedlings. Greenhouse experiment, using ICCRI 08 cocoa seedlings, was carried out in Kaliwining Experimental Station, Indonesian Coffee and Cocoa Research Institute, Jember, East Java. The LOF used for this experiment was made from about 1-month fermentation of cocoa pod waste in a 200 L plastic tank with additional biodecomposer to improve the biodegradation of organic materials. The experiment was designed by a completely randomized design (CRD), and taking into account two factors, i.e. the level of LOF concentration and urea application, as treatments of which their effect was determined through regular growth observations and laboratory determination. The variation of LOF concentration levels are (i) control (B0), (ii) LOF 0.25% (B1), (iii) LOF 0.50% (B2), and (iv) LOF 1% (B3). Additionally, the rates of urea applications include control (P0), 10% of fertilizer recommendation dosage (P1), 25% of fertilizer recommendation dosage (P2), and 50% of fertilizer recommendation dosage (P3). SPAD readings indicate the significant effect of urea and its combination with LOF to the increase in the chlorophyll content by 10 – 20% in compare to control. The total N uptake by cocoa tends to decrease with the increase in the concentration of LOF. With average increase of about 28% compared to control, statistical analysis suggest the insignificant different effect of treatments. The effect of LOF to the increase in the NUE, ranging from 0.50 to 0.80, in combination with specific level of urea. With 50% of urea recommendation dosage, the increase in NUE is above 40% up to 55% compared to non-LOF applied treatments. REN data interpretation indicates the higher of its values for treatments with lower level of urea applications. With the increase in the urea rate, the REN value is decreasing implying the contribution from the input of N. In this level, the REN is down to below 50% showing the lower amount of N required in compare to the N inputs. Relating the dosage of urea with N uptake shows an asymptotic type of curves. It indicates the optimal rate of urea ranging from 0.5 to 1 g urea per pot. The higher amount of LOF applied shows to decrease the optimal dosage of urea required in compare to no LOF application (B0). Though its use as source of nutrients is limited, current research may indicate the potential utilization of LOF through foliar spray to increase the efficiency of urea application.